8x-3-9x+9=2x-3x+3

Simple and best practice solution for 8x-3-9x+9=2x-3x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-3-9x+9=2x-3x+3 equation:


Simplifying
8x + -3 + -9x + 9 = 2x + -3x + 3

Reorder the terms:
-3 + 9 + 8x + -9x = 2x + -3x + 3

Combine like terms: -3 + 9 = 6
6 + 8x + -9x = 2x + -3x + 3

Combine like terms: 8x + -9x = -1x
6 + -1x = 2x + -3x + 3

Reorder the terms:
6 + -1x = 3 + 2x + -3x

Combine like terms: 2x + -3x = -1x
6 + -1x = 3 + -1x

Add 'x' to each side of the equation.
6 + -1x + x = 3 + -1x + x

Combine like terms: -1x + x = 0
6 + 0 = 3 + -1x + x
6 = 3 + -1x + x

Combine like terms: -1x + x = 0
6 = 3 + 0
6 = 3

Solving
6 = 3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 28/4=x/47 | | 0.45(m+25)=0.25(m+40) | | B+200=580 | | (x-12)(x-12)=17 | | 3x+9x-4=5+3(2x-7) | | 4x+32=128 | | 13-(-2x-5)=8 | | mx+ny=46 | | 7x-18=5x+2 | | 5=v+6 | | F(x)=(2x+5)(x-1) | | .15(x-4)=9.9-.3(x-1) | | dy/dx=x^6y^-5 | | 94=-2x-6+12 | | 6(2x-1)x-12=3(7x+6) | | (x+4)(5x-4)=o | | 625^(3/4) | | 32^(1/5) | | -4(y+6)=-4y-23 | | 4(x-5)-3x/4=2/5 | | -4.2v+6.1=2.1v+4 | | 7x-40y=-146 | | 7(4m+8)=-32+6m | | -6u-5=2u-13 | | -4z+18=3(2z-4) | | x^3-36x^2+432x-1735=0 | | 2(1+6p)=13+p | | -7w-17=1 | | 7x-(4)+9x-(40)=180 | | -w-13=3w-1 | | 9=-2t-3 | | -2y+4=0 |

Equations solver categories